PENILAIAN OTOMATIS UJIAN ESSAY ONLINE BERBASIS ALGORITMA RABIN KARP - Saeful Bahri (Universitas Bina Sarana Informatika Kota Sukabumi, 2014)
The development of today's computers have spurred each activity to be applied into the computer system. The purpose of it is to replace the manual systems that occur in everyday life. One of the activities that can be applied in a computer system is a system of checks scope of academic essay exam. Exam essay is a set of questions or orders given tomeasure the degree of one's understanding of the material. Function examination essay exam is to be able to describe the level of understanding in the form of numbers or so called value. In the essay exam inspection process is still done by hand so that it less effective and less objective than that it took quite a long time. To resolve such issues in this study a Rabin Karp algorithm is implemented using the PHP language Rabin Karp Algorithm.